The impact of a hazardous external environment on the quality of life, physical activity, and health of students in Ukraine, Poland, and Romania - Potop, Vladimir; Vypasniak, Igor; Ivanyshyn, Iryna; Lutskyi, Vasyl; Kryventsova, Iryna; Shesterova, Lyudmila; Prusik, Krzysztof (My University, 2024)
Background and Study. Aim The issue of quality of life, physical activity, and health of students is becoming increasingly relevant in the context of the ongoing conflict in Ukraine. Daily shelling of cities and settlements for over two years may have significantly affected the quality of life of Ukrainian students. While students in Poland and Romania do not experience the direct impact of military actions, regional instability and mass migration processes may also influence their health and well-being. In this context, the aim of the study is to identify key trends and issues related to the quality of life and health of students in Ukraine, Poland, and Romania. Material and Methods. The study involved students from Ukraine (n=193), Poland (n=40), and Romania (n=215). The SF-36 questionnaire, adapted into three languages: Ukrainian, Polish, and Romanian, was used to assess quality of life. Data collection was conducted online. The results were processed using PyCharm CE and specialized Python codes with relevant libraries. Cronbach’s alpha coefficient (α Cronbach’s = 0.765) was used to assess the internal consistency of the questionnaire responses. Factor analysis was conducted, with the number of factors (8) determined using the Kaiser criterion. The MannWhitney U test was used. Mean values, standard deviations, and percentage ratios were calculated. The significance level was set at 0.05. Results Data analysis revealed significant differences in quality of life, physical activity, and health of students depending on the country and gender. Ukrainian students, affected by the ongoing conflict, showed a substantial decrease in mental health indicators. The average mental health score for Ukrainian female students was 25.42%, and for male students, it was 23.92%. This indicates high levels of stress and anxiety caused by constant threats and instability. Polish students are older than Romanian and Ukrainian students, with the highest indicators of height and weight. In Poland, women reported better mental health (58.67±15.94) compared to men (55.09±12.82). Men demonstrated better physical health indicators (50.50±6.96) compared to women (47.58±6.57). In Romania, men showed better results in the psychological health component (42.79±8.61) compared to women (39.67±8.70) and higher physical functioning scores. Conclusions. The results of the analysis highlight that the war in Ukraine significantly impacts the physical and mental health of Ukrainian students. The considerable cross-country differences in student health indicators underscore the need to consider the specific conditions and challenges faced by students in different countries. These differences are particularly important for developing targeted programs that can effectively support students in wartime conditions.
Potop V., Vypasniak I., Ivanyshyn I., Lutskyi V., Kryventsova I., Shesterova L., Prusik K. The impact of a hazardous external environment on the quality of life, physical activity, and health of students in Ukraine, Poland, and Romania / V. Potop, I. Vypasniak, I. Ivanyshyn, V.Lutskyi, I. Kryventsova, L. Shesterova, K. Prusik // Pedagogy of Health. – 2024. – №2. – С. 57-69.
Keywords: СФ-36, стрес, тривога, воєнний час, самопочуття; SF-36, stress, anxiety, wartime conditions, well-being